Conducting research in juvenile and criminal justice settings - Vaughn, Michael G.; Pettus-Davis, Carrie; Shook, Jeffrey J. (New York ; Oxford : Oxford University Press, 2012)
This pocket guide provides state-of-the-art techniques for researchers, graduate students, and agency administrators. Readers will encounter a wide range of study types and data sources, along with strengths and weaknesses to consider with each as they conceptualize, implement, and analyze their research.
Series from CIP print version.
Description based on online resource; title from PDF title page (viewed on May 15, 2012).
Includes bibliographical references.
Keywords: Juvenile justice, Administration of -- Research -- United States; Juvenile delinquency -- Research -- United States; Criminal justice, Administration of -- Research -- United States; Social service -- Research